2021
DOI: 10.3389/fmicb.2021.621564
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Drug Resistance and Class 1 Integrons in Escherichia coli Isolated From River Yamuna, India: A Serious Public Health Risk

Abstract: Globally, urban water bodies have emerged as an environmental reservoir of antimicrobial resistance (AMR) genes because resistant bacteria residing here might easily disseminate these traits to other waterborne pathogens. In the present study, we have investigated the AMR phenotypes, prevalent plasmid-mediated AMR genes, and integrons in commensal strains of Escherichia coli, the predominant fecal indicator bacteria isolated from a major urban river of northern India Yamuna. The genetic environment of blaCTX–M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…To date, this is the first report of detection of strA gene in Philippine waters. Similar findings of the occurrence of strA gene were reported in waterborne (Gomi et al 2017;Singh et al 2021) and foodborne E. coli isolates (Zhang et al 2014;Poirel et al 2018) in several countries.…”
Section: Resultssupporting
confidence: 87%
“…To date, this is the first report of detection of strA gene in Philippine waters. Similar findings of the occurrence of strA gene were reported in waterborne (Gomi et al 2017;Singh et al 2021) and foodborne E. coli isolates (Zhang et al 2014;Poirel et al 2018) in several countries.…”
Section: Resultssupporting
confidence: 87%
“…In this study, integrons were found in 44.77% of the tested isolates, which is similar to other studies [10,12]. Several studies, on the other hand, found a higher prevalence rate of integrons [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, integrons were found in 44.77% of the tested isolates, which is similar to other studies [ 10 , 12 ]. Several studies, on the other hand, found a higher prevalence rate of integrons [ 33 35 ]. The present study revealed the predominance of integron I among quinolone-resistant isolates (59/80 isolates, 73.75%).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ARG-specific identification revealed that basic gene sets (sul1 and ∆qacE) in the class 1 integron were predominant in the detected ARGs (Figure 4A), suggesting that the class 1 integron plays a pivotal role for HGT among environmental bacteria and human pathogens. 24 Here, we did not completely investigate all the cassette genes in possible class 1 integrons. However, most AMG resistance genes (aadA and aph gene families), MAC resistance genes [msr(E) and mph(E)], and some β-lactamase genes, such as OXA-type carbapenemase, are cassette gene components in class 1 integron.…”
Section: Dovepressmentioning
confidence: 99%